Optimization of Intracellular Genetic and Non-genetic Cargo Delivery using Clinical Ultrasound and Microbubbles - Joshi, Kushal; Tsai, Scott; Lee, Warren (CMBES Proceedings, 2023)
I. INTRODUCTION Targeted delivery of drugs, genes and siRNA using ultra-sound and microbubbles (USMB) has emerged as a promis-ing approach for treating diseases such as cancer and acute respiratory distress syndrome (ARDS).1 Optimization of ultrasound settings and microbubble concentration is criti-cal for achieving high efficiency of intracellular cargo delivery. However, currently there are no systematic opti-mization studies investigating how different clinical ultra-sound system settings and microbubble parameters affect the efficiency of genetic and non-genetic cargo delivery. In this work, we show how different clinical ultrasound set-tings and microbubble concentration affect intracellular delivery of model drugs such as fluorescent dextran and model genetic cargoes such as fluorescent siRNA and plasmids using a novel, 3D-printed, modular platform for USMB studies. II. METHODS For systematic optimization of different cargo delivery parameters, a standardized, 3D-printed, modular platform called ultrasound-microbubble-cell chamber (UMCC) is developed.1 UMCC is designed on the concept of modulari-ty and consists different pre-designed blocks that snap-fit into each other to form the complete platform, analogous to LEGO® blocks. We use a commercial Phillips SONOS 5500 ultrasound system with Phillips S3 transducer, as well as commercial DEFINITY® microbubbles for optimization studies. As a model drug, we use 4 kDa FITC dextran and 70 kDA tetramethylrhodamine dextran. We also use Alexa Fluor 488 tagged-siRNA as well as green-fluorescent pro-tein (GFP) plasmids as model genetic cargoes. We study the effect of different clinical ultrasound parameters, spe-cifically mechanical index (MI), pulse interval (PI), ultra-sound exposure time as well as DEFINITY® microbubble concentration on efficiency of cargo delivery. MI is varied from 0.1 to 1.3, PI is varied from 200 ms to 5000 ms, ultra-sound exposure time is varied from 20 seconds to 80 sec-onds and microbubble concentration is varied from 8 x 105 bubbles/mL to 2.4 x 109 bubbles/mL. Experiments are done with HEK293 and CMT167 cell lines and cargo delivery is quantified using flow cytometry. III. RESULTS We discovered that the efficiency of cargo delivery in-creases with increasing MI, with highest delivery efficien-cy obtained at MI of 1.3. Cargo delivery was observed to decrease with increasing PI with highest delivery efficien-cy at PI of 200 ms. Moreover, we found that the cargo delivery increased 3-fold when ultrasound exposure time is increased from 20 seconds to 40 seconds. Increasing expo-sure time beyond 40 seconds did not significant change the efficiency of cargo delivery. We also found that cargo delivery peaks in a narrow range of DEFINITY® mi-crobubble concentration, ranging from 4 x 107 to 1.6 x 108 bubbles/mL. IV. CONCLUSION Our results show that different parameters such as MI, PI, exposure time and microbubble concentration affect intracellular delivery of cargo using USMB-delivery and these parameters can be optimized for maximizing the efficacy of cargo delivery in vitro. These optimum parameters could be potentially used for maximizing delivery of cargo in in vivo animal models. ACKNOWLEDGEMENTS We thank Monika Lodyga from the Research Core of Keenan Research Centre for Biomedical Science for help with flow cytometry. We also acknowledge funding from Natural Sciences and Engineering Research Council (NSERC). REFERENCES 1. K. Joshi, R. Sanwal, K. Thu, S.S.H. Tsai and W.L. Lee, “Plug and Pop: A 3D-Printed, Modular Platform for Drug Delivery Using Clinical Ultrasound and Microbubbles,” Pharmaceutics, 14(11), 2516, 2022.